Fluency in Dialogue: Turn‐Taking Behavior Shapes Perceived Fluency in Native and Nonnative Speech. Issue 4 (17th June 2020) - van Os, Marjolein; de Jong, Nivja H.; Bosker, Hans Rutger
Abstract: Fluency is an important part of research on second language learning, but most research on language proficiency typically has not included oral fluency as part of interactions even though natural communication usually occurs in conversations. The present study considered aspects of turn‐taking behavior as part of the construct of fluency and investigated whether these aspects differentially influence perceived fluency ratings of native and nonnative speech. Results from two experiments using acoustically manipulated speech showed that, in native speech, too "eager" answers (interrupting a question with a fast answer) and too "reluctant" answers (answering slowly after a long turn gap) negatively affected fluency ratings. However, in nonnative speech, only too "reluctant" answers led to lower fluency ratings. Thus, we demonstrated that acoustic properties of dialogue are perceived as part of fluency. By adding to the current understanding of dialogue fluency, these lab‐based findings carry implications for language teaching and assessment. Abstract :